How does principal’s instructional leadership shape teacher performance mediated by teacher self-efficacy in Indonesian education context? - Elfira,; Rasdiana,; Fitrawati,; Jasman, Muh Wahyudi; Reski, Kiki; Anwar, Amriyadi; Enaldi, (Frontiers in Education, 2024)
This study seeks to examine the relationships among principal instructional leadership (PIL), teacher self-efficacy (TSE), and teacher performance (TP) within the Indonesian educational setting. Employing a quantitative approach utilizing Partial Least Square Structural Equation Modeling (PLS-SEM), this research involved a sample of 127 productive teachers randomly selected from 247 teachers in schools implementing the Merdeka Belajar curriculum. Surveys were administered to measure perceptions of PIL, TSE, and TP. Additionally, relevant literature was reviewed to provide theoretical frameworks and research hypotheses. The findings reveal significant direct relationships between PIL and both TSE (0.721) and TP (0.598), indicating that strong instructional leadership positively influences teachers' self-efficacy and performance. Moreover, TSE is found to directly impact TP (0.358), suggesting that teachers' beliefs in their capabilities play a crucial role in their instructional practices and outcomes. Furthermore, TSE is identified as a significant mediating in the relationship between PIL and TP (0.258), highlighting the importance of fostering teachers' self-efficacy to enhance their performance indirectly through instructional leadership. Ultimately, this research highlights the crucial significance of instructional leadership in influencing school culture, which ultimately affects teacher confidence and facilitates teacher performance. By understanding the mechanisms through which PIL impacts TSE and TP, educational leaders can implement strategies to foster a supportive environment that empowers teachers.